Pengaruh Zakat, Infak dan Sedekah Terhadap Kesejahteraan Mustahik di Baznas Kota Tangerang di Masa Pandemi Covid-19 - Khumaini, Sabik; Abdullah, Muhammad Dinal; Warto, Warto (Al Maal: Journal of Islamic Economics and Banking, 2023)
This study aims to determine the effect of zakat, infaq and alms on the welfare of mustahik in the BAZNAS Tangerang City during the COVID-19 pandemic. This type of research is a quantitative approach. The data used is primary data obtained based on respondents' answers to the questionnaire distributed by researchers to mustahik in BAZNAS Tangerang City. The data analysis method uses the Classical Assumption Test which includes the Normality Test, Multicollinearity Test, Heteroscedasticity Test, Autocorrelation Test, Multiple Regression Analysis, F Test, Adjusted R Square Test, and t Test. The results of this study indicate that partially Zakat has a significant positive effect on the welfare of mustahik. Infaq has a significant positive effect on the welfare of mustahik. Alms have a significant positive effect on the welfare of mustahik. Furthermore, simultaneously zakat, infaq and alms have a significant positive effect on mustahik with a level of significance of less than 5%. Meanwhile, based on (R2), it can be seen that the value of Adjusted R Square is 84.5%. It means that the ability of the independent variable to explain the variance of the dependent variable is 84.5% and 15.5% is explained by other variables.